"Пізньоскіфські" чи "постскіфські" городища Нижнього Подніпров’я - Гаврилюк, Н.О.; Матера, М. (Археологія, 2016)
У статті йдеться про дискусію щодо «пізньоскіфських» або «постскіфських» пам’яток Нижнього Подніпров’я. Наводяться аргументи про неточність терміну «пізньоскіфські» — з точки зору термінології та з огляду на археологічне «наповнення» постскіфських пам’яток. This is a discussion on «Late Scythian» or «Post-Scythian» sites of the Lower Dnipro region. Presented are the arguments for the incorrectness of the term «Late Scythian» with relation to the terminology and the archaeological «filling» of the post-Scythian sites. Listed are the examples of improper dual usage of the term «Late Scythian» to sites of the second half of the 4th and the first half of the 3rd century BC and at the same time to sites of the period from the 2nd century BC to the 2nd century AD. This is unacceptable in respect to scientific terminology system. Some aspects of the material culture of hill-forts in the Dnipro River lower region not allowing to refer them to the settled Scythians’ sites are discussed. Речь идет о дискуссии о «позднескифских» или «постскифских» памятниках Нижнего Поднипровье. Приводятся аргументы о неточности термина «позднескифские» — с точки зрения терминологии и со стороны археологического «наполнения» постскифских памятников. Приводятся примеры неуместного двойного использования понятия «позднескифский» к памятникам второй половины IV — первой половины III вв. до н. э. и, в то же время, — к памятникам II в. до н. э. — II вв. н. э., что с точки зрения научной терминологической системы не допустимо. Рассматриваются некоторые аспекты материальной культуры городищ Нижнего Поднипровья, которые не позволяют относить их к скифских памятникам оседлости.